Integration of cooperative sensing and transmission: Performance evaluation of cooperation strategies in cognitive radio - Rashid R.A.; Aripin N.M.; Fisal N.; Ariffin S.H.S.; Yusof S.K.S. (2023)
Cooperative communication is increasingly regarded as a way to address the hidden terminal issues and to improve the spatial diversity for the same spectrum frequency band. In this article, we investigate two cooperation strategies: cooperative sensing and cooperative transmission. The performance of OR and AND fusion schemes is compared in the former, while the performances in terms of achievable data rates are evaluated in the latter for cooperative transmission of primary traffic by cognitive users (CUs; cognitive relaying) and cooperative transmission between cognitive nodes. The first scenario focuses on system cooperation by power allocation while the second one on cooperation by bandwidth allocation. 2010 IEEE.